Bullous Lung Disease (BLD): A Narrative Literature Review - Gibran, Muhamad Aqil; Oea Khairsyaf; Afriani Afriani (HM Publisher, 2024)
Bullous lung disease (BLD) is often associated with spontaneous pneumothorax, but its role as a predisposing factor for recurrent pneumothorax is still not clearly revealed. Many factors are associated with lung BLD, but because BLD cases are still quite rare, efforts need to be made research further to find out more about the relationship between predisposing factors and BLD. Diagnosis of BLD by paying attention to the history, physical examination and appropriate radiological examination is necessary to determine whether surgery is necessary or not. Management of BLD has now developed with many different therapy options. The choice of invasive or non-invasive procedures is adjusted to clinical needs, equipment availability and medical personnel. Good treatment will of course provide satisfactory results, especially in terms of improving the patient's quality of life.